Search for excited electrons singly produced in proton-proton collisions at √s=13 TeV with the ATLAS experiment at the LHC - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Giulini, Maddalena; et al. (The European physical journal. C, Particles and fields, 2019)
A search for excited electrons produced in pp collisions at root s = 13 TeV via a contact interaction q (q) over bar -> ee* is presented. The search uses 36.1 fb(-1) of data collected in 2015 and 2016 by the ATLAS experiment at the Large Hadron Collider. Decays of the excited electron into an electron and a pair of quarks (eq (q) over bar) are targeted in final states with two electrons and two hadronic jets, and decays via a gauge interaction into a neutrino and a W boson (nu W) are probed in final states with an electron, missing transverse momentum, and a large-radius jet consistent with a hadronically decaying W boson. No significant excess is observed over the expected backgrounds. Upper limits are calculated for the pp -> ee* -> eeq (q) over bar and pp -> ee* -> e nu W production cross sections as a function of the excited electron mass m(e)* at 95% confidence level. The limits are translated into lower bounds on the compositeness scale parameter Lambda of the model as a function of m(e)*. For m(e)* < 0.5 TeV, the lower bound for Lambda is 11 TeV. In the special case of m(e)* = Lambda, the values of m(e)* < 4.8 TeV are excluded. The presented limits on Lambda are more stringent than those obtained in previous searches.
ATLAS Collaboration: M. Aaboud, C.F. Anders, V. Andrei, C. Antel, A.E. Baas, O. Brandt, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M.P. Geisler, M. Giulini, P. Hanke, L. Helary, J. Jongmanns, M. Kolb, A. Kugel, M. Lisovyi, H. Meyer zu Theenhausen, F. Napolitano, D.I. Narrias Villar, M. Şahinsoy, A. Schöning, H.-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, J. Wang, S.M. Weber, M. Wessels, X. Yue
Im Titel steht das s unter dem Wurzelsymbol
Gesehen am 02.01.2019